2013
DOI: 10.4236/abb.2013.412143
|View full text |Cite
|
Sign up to set email alerts
|

A ConA-like lectin isolated from <i>Canavalia maritima</i> seeds alters the expression of genes related to virulence and biofilm formation in <i>Streptococcus mutans</i>

Abstract: Bacteria form biofilms as an adaptive mechanism in response to environmental changes. Streptococcus mutans is the biofilm-forming bacterium that is primarily associated with dental caries. The expression of important genes by bacteria in biofilms is different from that of planktonic cells. Lectins are proteins that bind specifically to carbohydrates and may have important biological activities on bacterial cells, acting as antibacterial and anti-biofilm agents. ConM (Canavalia maritima lectin) is a protein tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Cavalcante et al . () showed that Streptococcus mutans cells treated with Canavalia maritima lectin (ConM) had reduced expression of genes related with biofilm formation and regulation as well as drug resistance. A lectin from the haemolymph of crab Portunus pelagicus was able to reduce biofilm thickness of Citrobacter amalonatius , Proteus vulgaris , P. aeruginosa and V. parahaemolyticus in 62, 90, 75 and 88%, respectively, with disruption of biofilm architecture (Jayanthi et al .…”
Section: Microbial Qs Biofilms and Lectinsmentioning
confidence: 99%
“…Cavalcante et al . () showed that Streptococcus mutans cells treated with Canavalia maritima lectin (ConM) had reduced expression of genes related with biofilm formation and regulation as well as drug resistance. A lectin from the haemolymph of crab Portunus pelagicus was able to reduce biofilm thickness of Citrobacter amalonatius , Proteus vulgaris , P. aeruginosa and V. parahaemolyticus in 62, 90, 75 and 88%, respectively, with disruption of biofilm architecture (Jayanthi et al .…”
Section: Microbial Qs Biofilms and Lectinsmentioning
confidence: 99%
“…Other mechanisms cited in studies that report antibiofilm activity of lectins involve their binding to constituents of the biofilm exopolymeric matrix, interrupting its polymerization and as anti‐ quorum sensing molecules, preventing the expression of genes required for biofilm development and for other virulence factors (Cavalcante et al . ; Klafke et al . ; Hasan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interactions between bacterial cells and lectins may also be linked to the inhibitory effect on biofilm formation by preventing the interactions between bacterial polysaccharides and surfaces as well as between other bacterial cells. Other mechanisms cited in studies that report antibiofilm activity of lectins involve their binding to constituents of the biofilm exopolymeric matrix, interrupting its polymerization and as anti-quorum sensing molecules, preventing the expression of genes required for biofilm development and for other virulence factors (Cavalcante et al 2013;Klafke et al 2013;Hasan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santi-Gadelha and colleagues (2006), using electron microscopy, observed the pre- Cavalcante et al 2561 sence of pores and severe disruption of bacterial membrane of Gram-positive, confirming the marked antimicrobial activity and pointing a possible mechanism of growth inhibition by lectins, since these pores formed in the membrane allows the output of the cell content (Terras et al, 1993;. By the genetic expression analysis of genes related to the S. mutans biofilm on Canavalia maritime lectin, Cavalcante et al (2013) observed that although the mechanism of action of these lectins requires a better understanding, the results reported in that present article suggest that ConM acts by starting or interrupting intracellular signaling pathways that culminate with the lowest expression of genes associated with virulence and biofilm formation in S. mutans.…”
Section: Lectins Action On Biofilms Mechanismsmentioning
confidence: 90%